Стан сильного душевного хвилювання у визначенні меж необхідної оборони від насильницького статевого злочину - Андрусяк, Ганна Миколаївна; Andrusiak, H (СНУ ім. Лесі Українки, 2019)
Стаття присвячена аналізу статті 116 КК України для теоретичного вирішення питання про те, чи можливо уникнути стану сильного душевного хвилювання особі, яка захищає своє життя, здоров’я, статеву свободу, а також оцінки відношення законодавця до поведінки потерпілого при перевищенні меж необхідної оборони. Автор вважає, що негативний вплив стресових станів на свідомість і діяльність людини обумовлює необхідність ретельно аналізувати психологічний стан людини при розслідуванні і судовому розгляді справ про перевищення меж необхідної оборони, навіть якщо не виникає підозр, що протиправні дії вчинені в стані афекту. The article highlights the problem of determining the range limits of the required defense against violent sexual assault and the concept of state of strong emotional excitement (Article 116 of the Criminal Code of Ukraine). The author discusses the question of whether it is possible to avoid a state of extreme emotion for a person who protects her life, health, sexual freedom, etc. and also analyzes the position of the legislator regarding the behavior of the victim in case of excess of the necessary defense limits. According to the author's conclusions, the death of a person should be considered legitimate only in case of protecting one's own life or other persons from grave bodily injuries (including committing other crimes), rape and forced sexual satisfaction in an unnatural way, traditionally regarded as the most socially dangerous violent attacks/assaults. Consequently, when investigating and prosecuting cases of exceeding the limits of the necessary defense the negative influence of stress states on the consciousness and activity of a person necessitates careful analysis of the psychological state of a person, even if there is no doubt that the unlawful actions are committed in a state of affection.
State of Strong Emotional Excitement (Affection) as a Factor in Determining the Boundaries of the Necessary Self-defense against Sexual Assault
Keywords: життя; здоров’я; статева свобода; статева недоторканість; необхідна оборона; стан сильного душевного хвилювання; life; health; sexual freedom; sexual integrity; necessary defense; a state of strong emotional excitement